Hospital Admission Rate, Cumulative Hospitalized Days, and Time to Admission Among Older Persons With Substance Use and Psychiatric Conditions - Jemberie, Wossenseged Birhane; Padyab, Mojgan; McCarty, Dennis; Lundgren, Lena M. (Frontiers in Psychiatry, 2022)
Background Substance use among older persons occurs with medical and psychiatric comorbidities. This study examined the associations of substance use disorder (SUD), psychiatric, and dual diagnoses with 12-month cumulative hospitalized days, hospital admission rate and number of days to first hospitalization. Methods The cohort of 3,624 individuals (28.2% women) aged 50 years or older was assessed for substance use severity in 65 Swedish municipalities during March 2003—May 2017. Addiction Severity Index data were linked to hospital discharge records and crime statistics. The outcomes were a) 12-month cumulative hospitalized days; b) Hospital admission rate, and c) days to first hospitalization. Generalized linear regression techniques investigated associations between outcomes and SUD, psychiatric and dual diagnoses at admission. Results During 2003-2017, 73.5% of the participants were hospitalized. Twelve-month hospitalized days were positively associated with SUD (Incidence rate ratio (IRR) = 1.41, 95%CI: 1.26—1.58), dual diagnosis (IRR= 2.03, 95%CI: 1.74—2.36), and psychiatric diagnoses (IRR= 2.51, 95%CI: 2.09—3.01). Hospital admission rate was positively associated with SUD (IRR= 4.67, 95%CI: 4.28—5.08), dual diagnosis (IRR= 1.83, 95%CI: 1.64—2.04), and psychiatric diagnoses (IRR= 1.73, 95%CI: 1.55—1.92). Days to first hospitalization were negatively associated with SUD (IRR= 0.52, 95%CI: 0.47—0.58), dual diagnosis (IRR= 0.57, 95%CI: 0.50—0.65), and psychiatric diagnoses (IRR= 0.83, 95%CI: 0.73—0.93). The marginal effects of SUD and/or mental disorders increased with age for all outcomes, except for days to first hospitalization. Conclusions Three of four older persons assessed for substance use severity were later hospitalized. Substance use disorders, dual diagnoses and other mental disorders were the primary reasons for hospitalization and were associated with longer stays, earlier hospitalization, and repeated admissions. Sensitizing service providers to late life substance use and sharing data across the care continuum could provide multiple points of contact to reduce the risk of hospitalizations among older persons with problematic substance use.